Are food policies empowering women? Framework, measurement, and empirical evidence from India and Nigeria - Kyle, Jordan; Ragasa, Catherine (International Food Policy Research Institute, 2025)
The Sustainable Development Goals (SDGs) emphasize equal participation and empowerment of women in all levels of decisionmaking, yet frameworks and tools to measure and strengthen women's empowerment in policy spaces remain limited. Focusing on agrifood systems, this paper introduces a framework, metrics, and scoring method to track women’s empowerment in policy processes (WEAGov) and presents findings from pilot applications in India and Nigeria. The pilots draw on novel surveys with more than 200 agrifood organizations and policy experts across the public sector, private sector, civil society, and research communities in both countries. Across both countries, we find that agrifood policy documents incorporate gender priorities on paper but fall short in budgeting, implementation, and evaluation. Prevailing social attitudes and limited awareness of policies, regulations, and legal rights remain major constraints on women’s ability to engage meaningfully in policy processes. Women participate as staff and mid-level managers in agrifood organizations, but their representation at higher decision-making levels are limited. Expert assessments also highlight disconnects between formal roles and the actual influence women can exert over policy decisions. Gender-responsive budgeting processes are absent in Nigeria and weakly-institutionalized in India, where compliance has become procedural rather than transformative. These patterns reveal persistent bottlenecks in translating gender commitments into practice. By systematically tracking barriers and identifying entry points for reform, the WEAGov framework offers governments, researchers, and civil society organizations a practical tool to diagnose gaps in women’s empowerment in agrifood policy processes and to strengthen their inclusiveness and accountability.